Current and Best Clinical Engineering Practices In The United States - Subhan, Arif; Painter, Frank (CMBES Proceedings, 2023)
Clinical Engineering professionals in the United States (US) - Clinical Engineers and Biomedical Equipment Technicians (BMETs) play an important role in enhancing patient safety and managing the deployment and use of medical technology in healthcare organizations. This presentation will share best US practices in managing different aspects of clinical engineering including inventory control, incoming inspections, planned maintenance, pre-purchase evaluation, managing equipment service contracts, hazard and recall notification, equipment installation, repairs and upgrade, purchase request review, equipment replacement planning, device incident review, and regulatory compliance. The presentation will review the US clinical engineering education programs that educates and trains the clinical engineers and BMETs. The continuing education activities that help maintain and enhance these professionals so that they can effectively lead and execute complex medical technology projects and clinical engineering functions within the healthcare organization will be discussed. The voluntary peer-developed US Certification program that demonstrates the competency and professional recognition of Clinical Engineers and BMETs by an externally validated examination will also be presented.